KEPUASAN PASIEN TERHADAP KETEPATAN WAKTU PENYAJIAN MAKANAN PADA DIET JANTUNG DI BANGSAL JANTUNG RSUP DR. M. DJAMIL PADANG - Anggi Mariani; Musparni (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
One of the services for inpatients is the provision of food and drinks for patients that are tailored to the patient's condition based on clinical conditions, nutritional status, and body metabolic status. In the implementation of hospital meals, it is measured by the patient's food left on the plate (Plate Waste) is the leftover food served to the patient, but not consumed and expressed in the percentage of food served. Food waste is an indicator of the success of nutritional therapy provided by the hospital. Food on the patient's plate in the cardiac ward of Dr M Djamil Hospital Padang and there is often a delay in the time of giving food to patients. The purpose of this study was to assess patient satisfaction with the heart diet food served and the timeliness of serving food to patients. The research method used is descriptive analysis. Data collection techniques are observation, questionnaires and documentation. The results of the research that the author has done can be seen from the color, shape, presentation and level of maturity of the food, where the color is less attractive, the number of servings is not appropriate and the level of maturity is less.